Elisabeth Nowotny: Thunau am Kamp − Das frühmittelalterliche Gräberfeld auf der Oberen Holzwiese. (Prispevki: Karina Grömer, Martin Ježek, Mathias Mehofer, Erich Nau, Gabriela Ruß-Popa und Şirin Uzunoglu-Obenaus), 2018 - Pleterski, Andrej (Arheološki vestnik, 2019)
/